Identity in Information Behaviour Research: A Conceptual Analysis - Hicks, Deborah (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
Using a conceptual analysis approach, this study explores how identity has been conceptualized in the information behaviour literature. Findings indicate that researchers have employed three main approaches when conceptualizing identity: identity as personal project, identity and social groups, and identity as selfpresentation were the three most common conceptualizations of identity. The findings contribute to the identification of the key factors of information behaviour and suggest areas for future research.